The Effect of Mixed Dye Composition of Anthocyanin-Chlorophyll on DSSC Efficiency on TiO2/ZnO Semiconductors - Manurung, Renta Wendi; Nurhidayah, Nurhidayah; Deswardani, Frastica (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2024)
The effect of mixed dye composition of anthocyanin-chlorophyll on DSSC efficiency on TiO2/ZnO semiconductors aims to determine the effect of using dye containing anthocyanin-chlorophyll on the absorbance value and work efficiency value of Dye Sensitized Solar Cell (DSSC). The TiO2/ZnO was deposited using the doctor blade method and the dye was made using the maceration method. The counter electrode was made on FTO glass coated by calcined battery carbon with temperature in 450°C. The DSSC assembly was arranged in a sandwich shape. Then electrolyte is dripped in the middle of the DSSC layer. Characterization tests were carried out to determine the dye absorbance value and gap energy value using a UV-Vis spectrophotometer. DSSC efficiency testing uses current and voltage (I-V) characterization. DSSC testing was carried out using a multimeter with a light source from sunlight. The results of UV-Vis characterization showed that the highest absorbance value was obtained for the kale-mangosteen peel dye at a wavelength of 530 nm with an absorbance of 5.234%. The TiO2/ZnO gap energy obtained using the touch plot method is 2.42 eV. The highest efficiency value was obtained from the kale-mangosteen peel dye mixture of 0.0286%. There was an increase in the DSSC efficiency value when the dyes were combined.